Penguatan Edukasi Kesehatan Berbasis Faktor Risiko untuk Pencegahan dan Deteksi Dini Diare pada Balita - Simunati Simunati; Andi Fatmawati; Sitti Nurbaya (Celebes Health Journal, 2025)
Diarrhea remains a major cause of morbidity in toddlers and is often influenced by behavioral factors, sanitation, and maternal knowledge. This situation is also evident in the Mangasa Community Health Center (Puskesmas) work area, where the proportion of toddlers who are not exclusively breastfed remains high, clean water use is suboptimal, and the majority of mothers have low levels of knowledge regarding diarrhea prevention and early detection. Based on these conditions, this community service activity was conducted to improve the ability of mothers of toddlers to prevent and recognize early signs of diarrhea through risk-factor-based health education. The implementation method included counseling, interactive discussions, and demonstrations of clean and healthy living practices, with success measured through pre-post knowledge questionnaires, behavioral observations, and short interviews. The results of the activity showed an increase in mothers' understanding of the causes of diarrhea, the importance of exclusive breastfeeding, clean water use, and initial actions when toddlers experience diarrhea. Behavioral changes were also seen in handwashing practices and improved drinking water storage. These findings indicate that risk-factor-based health education is effective in strengthening diarrhea prevention efforts in toddlers and has the potential to have long-term impacts on family health.